Acceleration of singlet fission in an Aza-derivative of TIPS-pentacene - Herz, Julia; Buckup, Tiago; Paulus, Fabian; Bunz, Uwe H. F.; Motzkus, Marcus (The journal of physical chemistry letters, 2014)
The influence of the carbon to nitrogen substitution on the photoinduced dynamics of TIPS-pentacene was investigated by ultrafast transient absorption measurements on spin-coated thin films in the visible and in the near-infrared spectral region. A global target analysis was performed to provide a detailed picture of the excited-state dynamics. We found that the chemical modification has a high impact on the triplet formation and leads to shorter dynamics; hence it speeds up the singlet fission process. A faster relaxation from the singlet into the triplet manifold implies a higher efficiency because other relaxation channels are avoided. The air-stable aza-derivatives have the potential to exceed the energy conversion efficiency of TIPS-pentacene.